2003
DOI: 10.1055/s-0037-1613374
|View full text |Cite
|
Sign up to set email alerts
|

Compliance and stability of INR of two oral anticoagulants with different half-lives: a randomised trial

Abstract: SummaryThe aim of the study was to assess the respective roles of the half-life of elimination of oral anticoagulants and patient education as causes of instability of anticoagulation level in patients on oral anticoagulant therapy. Patients were randomised to receive either warfarin (long half-life) or acenocoumarol (short half-life) and either intensive or standard education, according to a factorial design. Instability of oral anticoagulant therapy was evaluated by the percentage of INRs and the time within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…A retrospective study focussing on self-managed patients found a higher TTR on phenprocoumon than on warfarin [15]. A French randomised controlled trial showed no difference in TTR between patients initiated with warfarin versus those with acenocoumarol, but INR variability was lower in the warfarin group [16]. This implies that phenprocoumon (with the longest halflife) might lead to a higher TTR than warfarin (with the intermediate half-life); warfarin, in turn, could cause a higher or similar TTR to acenocoumarol (with the shortest half-life).…”
Section: Plos Onementioning
confidence: 99%
“…A retrospective study focussing on self-managed patients found a higher TTR on phenprocoumon than on warfarin [15]. A French randomised controlled trial showed no difference in TTR between patients initiated with warfarin versus those with acenocoumarol, but INR variability was lower in the warfarin group [16]. This implies that phenprocoumon (with the longest halflife) might lead to a higher TTR than warfarin (with the intermediate half-life); warfarin, in turn, could cause a higher or similar TTR to acenocoumarol (with the shortest half-life).…”
Section: Plos Onementioning
confidence: 99%